2015
DOI: 10.1111/iwj.12489
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MMP and TIMP evaluation in patients with deep venous thrombosis: could they have a predictive role in the development of post‐thrombotic syndrome?

Abstract: Post-thrombotic syndrome (PTS) is a condition that can develop in about half of the patients with deep vein thrombosis (DVT) of lower limbs. In the present study, we evaluated the expression of inflammatory biomarkers in the early phases of DVT and their correlation with the onset of PTS. Patients were enrolled after the first episode of DVT and were followed up for 1, 4, 8, 12 and 18 months. At each visit, blood sample was collected to evaluate plasma levels of matrix metalloproteinase (MMP)-1,-2,-3,-7,-8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 48 publications
0
46
0
2
Order By: Relevance
“…De Franciscis et al (2015) demonstrated increased MMP-9 levels in the acute phase of DVT when compared to healthy controls. However, after a follow-up of 18 months, DVT patients presented similar MMP-9 levels to controls [45]. Our study evaluated patients with a mean time of 61 months after the last DVT episode and we found that DVT patients presented decreased MMP-9 levels when compared to no/mild PTS.…”
Section: Discussionmentioning
confidence: 48%
“…De Franciscis et al (2015) demonstrated increased MMP-9 levels in the acute phase of DVT when compared to healthy controls. However, after a follow-up of 18 months, DVT patients presented similar MMP-9 levels to controls [45]. Our study evaluated patients with a mean time of 61 months after the last DVT episode and we found that DVT patients presented decreased MMP-9 levels when compared to no/mild PTS.…”
Section: Discussionmentioning
confidence: 48%
“…Various MMPs patterns have been identified to indicate several stages within the disease. MMP‐2, MMP‐9 and NGAL (which is a protein belonging to the lipocalin family, with the ability to positively modulate the activities of MMP‐9) appear to be mostly involved in the acute phase of vascular disease (such as aneurysm rupture and pulmonary embolism) , while MMP‐1 and MMP‐8 appear to be primarily involved with chronic or irreversible complications of vascular disease (such as difficult‐to‐heal or infected venous ulcers and post‐thrombotic syndrome) .…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are a group of several multi-domain zinc-dependent enzymes that are involved in the remodelling of several components of ECM (24). In the vasculature, MMPs influence the migration, proliferation and apoptosis of vascular smooth muscle cells, endothelial cells and inflammatory cells, thereby affecting intima formation, atherosclerosis, aneurysms, varicose veins and its complications, such as venous ulceration and post-thrombotic syndrome (6)(7)(8)(9)(10)(11)(12)(13)(14)25,26). Various MMPs patterns have been identified to indicate several stages within the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent cohort study, patients with PTS showed higher levels of MMP‐1 and MMP‐8 during the acute phase of DVT compared to patients without PTS . MMP‐1 and MMP‐8 may be markers of fibrosis during the inflammatory process, and further studies are indicated to determine their role as potential biomarkers for PTS.…”
Section: Risk Factorsmentioning
confidence: 99%